A Study on Impact of Microfinance Institutions on Socio Economic Development of Saurashtran Women - Mehta, Hiren Prakashbhai (International Journal Labs, 2023)
Background: Microfinance in the global context is commonly referred to programmes meant for providing credit for self-employment and other financial and business services to poor persons. It is as same as extension of small loans to very poor for self-employment projects that generate income, allowing them to care for themselves and their families. Aim: The objective of the study is to analyze the present status of management of micro finance in Saurashtra and it is relation to impact of micro finance among women SHGs in the study area. Method: In the present study, both exploratory research and descriptive research have been used in accomplishing the objectives of the study. The researcher visited the various blocks on different dates and collected data from different self help groups. To analyze the primary data statistical tools such as Descriptive Analysis, Chi-square test, ANOVA, Garret ranking technique, Discriminate Function Analysis, Friedman Test Factor Analysis, Kendall's coefficient of concordance test, Kruskal-Wallis test, Neural network and Structural Equation Modeling have been used. Findings: The study conclude that a ailment of Microfinance loan from microfinance institutions is helpful in empowering women economically, socio-culturally and politically. The study also found that the beneficiaries have reasonable employment, increase in income and participation in household financial decision-making as compared to non-beneficiaries.